2015
DOI: 10.1111/ijd.13138
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis in elderly patients in the Côte d'Ivoire: socio‐demographic, clinical, and therapeutic aspects, and follow‐up

Abstract: Topical agents could be the first-line treatment in geriatric patients in poor countries. If necessary, systemic agents should be used by taking into account the severity of psoriasis, presence of comorbidity factors, immune system level, and lifestyle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Although the absolute number and incidence of events were high above 65 years and low under 65, individuals who develop psoriasis at younger ages (40-60 years) are more likely to develop AD than age-matched individuals who are not diagnosed with psoriasis. In this regard, previous studies have shown that aging promotes a decrease in T cell immune function thereby reducing inflammation and leads to suppress the development of skin inflammatory diseases, which may support our hypothesis [30][31][32] . Additionally, since elderly people have various chronic diseases such as diabetes mellitus, hypertension, hyperlipidemia and depression and take many kinds of drugs, the effect of psoriasis on the development of AD may be more sensitive in middle age than in older age 33,34 .…”
Section: Discussionsupporting
confidence: 88%
“…Although the absolute number and incidence of events were high above 65 years and low under 65, individuals who develop psoriasis at younger ages (40-60 years) are more likely to develop AD than age-matched individuals who are not diagnosed with psoriasis. In this regard, previous studies have shown that aging promotes a decrease in T cell immune function thereby reducing inflammation and leads to suppress the development of skin inflammatory diseases, which may support our hypothesis [30][31][32] . Additionally, since elderly people have various chronic diseases such as diabetes mellitus, hypertension, hyperlipidemia and depression and take many kinds of drugs, the effect of psoriasis on the development of AD may be more sensitive in middle age than in older age 33,34 .…”
Section: Discussionsupporting
confidence: 88%
“…All of our patients were diagnosed as having plaque-type psoriasis, consistent with previous studies reporting the plaque-type to be the most common type of psoriasis. 4,5,[9][10][11][12][13][14][15] The number of patients with other psoriasis types was too small for us to draw any conclusion. Nonetheless, a study in France observed a higher frequency of guttate and inverse psoriasis among patients aged > 70 years, 5) whereas a study in Côte d'Ivoire demonstrated an increasing tendency for pustular and inverse psoriasis among patients with elderly-onset psoriasis.…”
Section: Discussionmentioning
confidence: 90%
“…Nonetheless, a study in France observed a higher frequency of guttate and inverse psoriasis among patients aged > 70 years, 5) whereas a study in Côte d'Ivoire demonstrated an increasing tendency for pustular and inverse psoriasis among patients with elderly-onset psoriasis. 11) Compared with early onset psoriasis, late-onset psoriasis generally has a milder disease severity. 5,9) However, as we only included patients who received phototherapy, which is the treatment of choice for moderate-to-severe psoriasis, none of our patients had mild disease severity at baseline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature search returned a total of 145 publications and 10 of these described patients in Africa or the Middle East. Of these 10 publications, there were 4 research articles (Table 1), [20][21][22][23] 3 reviews (Table 2) Table 3), 26,27 and 1 case study (published in Hebrew). 28 Two of the 4 research articles described non-interventional studies and 2 reported data from studies on the safety and efficacy of phototherapy (1 in patients with plaque psoriasis localized to the scalp or palmoplantar areas and 1 in patients ≥65 years of age).…”
Section: Resultsmentioning
confidence: 99%